Ethical assessment of life-prolonging treatment - Winkler, Eva C.; Hiddemann, Wolfgang; Marckmann, Georg (The lancet. Oncology, 2011)
To investigate 1) younger (< 65) and older (> 65) adults’ preference for and understanding of graph formats presenting risk information, and 2) the contribution of age, health literacy, numeracy and graph literacy in understanding information. - To assess preferences, participants (n = 219 < 65 and n = 227>65) were exposed to a storyboard presenting six types of graphs. Understanding (verbatim and gist knowledge) was assessed in an experiment using a 6 (graphs: clock, bar, sparkplug, table, pie vs pictograph) by 2 (age: younger [<65] vs older [>65]) between-subjects design. - Most participants preferred clock, pie or bar chart. Pie was not well understood by both younger and older people, and clock not by older people. Bar was fairly well understood in both groups. Table yielded high knowledge scores, particularly in the older group. Lower age, higher numeracy and higher graph literacy contributed to higher verbatim knowledge scores. Higher health literacy and graph literacy were associated with higher gist knowledge. - Although not the preferred format, tables are best understood by older adults. - Graph literacy skills are essential for both verbatim and gist understanding, and are important to take into account when developing risk information.